Effect of the addition of nanoclays on the water absorption and mechanical properties of glass fiber/up resin composites. (June 2015) - Rull, N; Ollier, RP; Francucci, G; Rodriguez, ES; Alvarez, VA
Mechanical performance of composite materials must remain satisfactory during their life in service. However, composite structures such as wind blades are usually exposed to humid and severe environments, and the absorbed water can degrade the fiber–matrix interface decreasing the composite overall performance. Dual scale (nano-micro) composites can be obtained by adding nanoparticles to the polyester resin and reinforcing that nanomaterial with a glass fiber mat. These materials have good potential in the production of composite parts such as wind blades because nanoparticles dispersed in the polymer matrix could lower the water absorption of the composites and improve their performance in humid environments. However, nanosized reinforcing particles have high internal surface and therefore they tend to agglomerate and are difficult to disperse homogeneously in the polymeric matrix. Moreover, the final properties of the nanocomposites are strongly influenced by clay particles' morphology and dispersion. In this work, the effect of the addition of pristine and organomodified nanoclays on the water absorption and mechanical properties of glass fiber/unsaturated polyester resin composites was studied. Results showed that the chemical treatments were effective in improving clay dispersion, reducing water absorption, and increasing the composites' performance in humid environments. In addition, this work presents a procedure to use water absorption tests as means of accelerated humidity absorption tests.